2011
DOI: 10.1038/leu.2011.267
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome in infants with AML after intensive first- and second-line treatment: an AML-BFM study group report

Abstract: Infants o1 year of age have a high prevalence of prognostically unfavorable leukemias and a presumed susceptibility to treatment-related toxicities. A total of 125 infants with acute myeloid leukemia (AML) were treated in studies AML-BFM-98 (n ¼ 59) and -2004 (n ¼ 66). Treatment regimens of both studies were comparable, consisting of intensive induction followed by four courses (mainly high-dose cytarabine and anthracyclines). Allogeneic-hematopoietic stem-cell-transplantation (allo-HSCT) in 1st remission was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
3
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 35 publications
7
87
3
10
Order By: Relevance
“…The outcome for infants treated according to NOPHO-AML 2004 was excellent (5-year EFS: 66%, 95%CI: 46%-79%, 5-year OS: 82%, 95%CI: 63%-91%) and confirm previous reports showing favorable outcome for infants. 19,34 High-dose cytarabine seems safe and effective in treating infants with AML, and our results do not support further dose reductions in infants as recommended by others. 14 Children aged 10-17 years were at higher risk of toxicity.…”
Section: A B C Dcontrasting
confidence: 52%
See 2 more Smart Citations
“…The outcome for infants treated according to NOPHO-AML 2004 was excellent (5-year EFS: 66%, 95%CI: 46%-79%, 5-year OS: 82%, 95%CI: 63%-91%) and confirm previous reports showing favorable outcome for infants. 19,34 High-dose cytarabine seems safe and effective in treating infants with AML, and our results do not support further dose reductions in infants as recommended by others. 14 Children aged 10-17 years were at higher risk of toxicity.…”
Section: A B C Dcontrasting
confidence: 52%
“…To our knowledge, no previous studies have reported such a thorough review of toxicities and associations with age and body weight at diagnosis, though many studies suggest similar associations. 12,13,18,19,26,27 We found a trend for age 10-17 years being associated with poorer survival. In contrast to previous studies, 12,13 we found a trend for being overweight being associated with improved survival in children aged 10-17 years.…”
Section: © Ferrata Storti Foundationmentioning
confidence: 60%
See 1 more Smart Citation
“…В частности, транслокация t(1;12) (p15;q13) ассоциирована с М7-подтипом ОМЛ, трансло-кация (7;12)(q36;p13) обычно сопровождается трисо-мией 19-й хромосомы или реже трисомией 8-й хромо-сомы. Транслокации, вовлекающие 11-ю хромосому, обычно выявляются при миеломонобластном и моноб-ластном подтипе ОМЛ, причем глобальная встречае-мость 11q23/MLL варьирует в различных исследованиях у детей от 35 до 50 % [12,13].…”
Section: молекулярно-генетическая классификация острого миелобластногunclassified
“…As well as the predominance of MLL rearrangements, rare aberrations almost exclusively seen in this cohort include t(7;12)(MNX1/ETV6), [22] t(1;22)(RBM15(OTT)-MKL1(MAL)) [49] and inv(16)(CBFA2T3/GLIS2) [21], the latter two associated with non-DS AMKL. In contrast, CBF AML and APML are rare in infants [9,50]. Like GATA1 mutations in ML-DS, MLL rearrangements occur in utero evidenced by twin concordance studies [36] and by the detection of MLL rearrangements in patient matched leukaemic samples and newborn blood spots [37].…”
Section: Infant Amlmentioning
confidence: 99%